Mothers' Use of Social Media to Inform Their Practices for Pumping and Providing Pumped Human Milk to Their Infants - Rei Yamada; Kathleen M. Rasmussen; Julia P. Felice (MDPI AG, 2016)
Despite U.S. mothers' wide adoption of pumps and bottles to provide human milk (HM) to their infants, mothers lack comprehensive, evidence-based guidelines for these practices. Thus, some women use online sources to seek information from each other. We aimed to characterize the information women sought online about pumping. We used data provided by ~25,000 women in an open cohort within a discussion forum about parenting. We examined 543 posts containing questions about providing pumped HM cross-sectionally and longitudinally in three time intervals: prenatal, 0 through 1.5 months postpartum, and 1.5 to 4.5 months postpartum. We used thematic analysis with Atlas.ti to analyze the content of posts. During pregnancy, women commonly asked questions about how and where to obtain pumps, both out-of-pocket and through insurance policies. Between 0-1.5 months postpartum, many mothers asked about how to handle pumped HM to ensure its safety as fed. Between 1.5-4.5 months postpartum, mothers sought strategies to overcome constraints to pumping both at home and at work and also asked about stopping pumping and providing their milk. Women's questions related to ensuring the safety of pumped HM represent information women need from health professionals, while their questions related to obtaining pumps suggest that women may benefit from clearer guidelines from their insurance providers. The difficulties women face at home and at work identify avenues through which families and employers can support women to meet their goals for providing HM.